2023
DOI: 10.1186/s40364-023-00493-6
|View full text |Cite
|
Sign up to set email alerts
|

The role and metabolic adaptations of neutrophils in premetastatic niches

Abstract: It has been found that tumor cells create microenvironments in distant organs that promote their survival and growth in advance of their arrival. These predetermined microenvironments are referred to as “pre-metastatic niches”. Increasing attention is being paid to neutrophils’ role in forming the pre-metastatic niche. As major components of the pre-metastatic niche, tumor-associated neutrophils (TANs) play an important role in the formation of the pre-metastatic niche through communication with multiple growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…It has been well established that the neutrophil chemokine axis CXCR4/CXCL12 is crucial in recruiting neutrophils to the pre‐metastatic niche such as in breast cancer, 60 and CXCL12 is upregulated in several different metastatic sites as reviewed by Chen and Yu. 61 This review reported illustrates the importance of the CXCR2‐dependent recruitment of neutrophils and the role of CXCL5 in promoting both recruitment of neutrophils to lymph nodes as well as lymph node metastasis. Furthermore, the stromal cell‐derived factor 1 (SDF1/CXCL12)‐CXCR4 axis also contributes to neutrophil recruitment to the liver pre‐metastatic niche.…”
Section: The Unique Features Of Neutrophilsmentioning
confidence: 96%
“…It has been well established that the neutrophil chemokine axis CXCR4/CXCL12 is crucial in recruiting neutrophils to the pre‐metastatic niche such as in breast cancer, 60 and CXCL12 is upregulated in several different metastatic sites as reviewed by Chen and Yu. 61 This review reported illustrates the importance of the CXCR2‐dependent recruitment of neutrophils and the role of CXCL5 in promoting both recruitment of neutrophils to lymph nodes as well as lymph node metastasis. Furthermore, the stromal cell‐derived factor 1 (SDF1/CXCL12)‐CXCR4 axis also contributes to neutrophil recruitment to the liver pre‐metastatic niche.…”
Section: The Unique Features Of Neutrophilsmentioning
confidence: 96%
“…These predetermined microenvironments are commonly referred to as pre-metastatic niches. 11 , 105 Pre-metastatic niches are established through systemic signals emanating from the primary tumor prior to the arrival of cancer cells, which recruit supportive stromal cells and other cellular constituents. The perivascular microenvironment facilitates the extravasation of cancer cells and their dissemination along the basement membrane of capillaries.…”
Section: Colorectal Cancer-derived Exosomesmentioning
confidence: 99%
“…Exosome-mediated intercellular communication plays a crucial role in various critical steps of metastatic colorectal cancer (mCRC) development and progression, including enhancing tumor cell invasion and migration capacity, altering vascular permeability, facilitating immune escape, and promoting pre-metastatic niche formation. 9 , 10 , 11 Exosomes also act as triggers or drivers for tumor metastasis occurrence when interacting with other factors. 6 , 12…”
Section: Introductionmentioning
confidence: 99%
“…In addition to immune cells, some studies have suggested that tumor cells themselves might acquire the ability to produce IL-17A under certain conditions or in specific types of tumors. For example, colorectal and breast cancers are capable of producing IL-17 to guide IL-17R-positive neutrophils’ directional migration [ 5 ]. IL-17A targets various cells which contain its receptor, composed of IL-17RA and IL-17RC dimers, which results in host defense, chronic inflammation, tissue destruction and repair, and oncogenesis [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%